Toronto Farmers' Markets: Towards Cultural Sustainability? - Deborah Bond; Robert Feagan (Journal of Agriculture, Food Systems, and Community Development, 2016)
This paper accomplishes two interrelated objectives. The first is a qualitative assessment of the level of interest and accommodation of culturally appropriate foods at 14 farmers' markets (FMs) within the multicultural urban core of Toronto, Ontario. The second objective acquires insights from key public "food commentators" and from new agricultural initiatives in this region that help us develop recommendations relative to the outcomes of the first objective. Results from the first part of the study indicate that the level of provision of culturally appropriate foods at these FMs in Toronto is at an embryonic stage. The results of the second part of the study point to a range of initiatives oriented to support increased provision and accommodation of culturally appropriate foods along the FM chain, while also pointing to the existing constraints to these efforts. Broad recommendations include supporting emerging agricultural innovations and the diversity of partnership possibilities in this work; increasing awareness of such efforts for cultural sustainability objectives; and attending to FM vendor needs around this shift in demand. Policy efforts could focus on incentives and training for agricultural nonprofits and for partnership building, on supporting cultural groups hoping to increase their access to such foods grown in this region, and on existing farmers and those interested in farm access for these purposes. At the same time, advocacy for such shifts needs to recognize challenges in Canada to growing such new crops, the reality of farmer/vendor bottom lines, and broader global food system realities that constrain such efforts.